2020
DOI: 10.1021/acsnano.0c02294
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Defect-Rich Hierarchically Porous Carbon Architectures Enabling Enhanced Capture and Catalytic Conversion of Polysulfides

Abstract: Despite their promising potential, the real performance of lithium-sulfur batteries is still heavily impeded by the notorious shuttle behavior and sluggish conversion of polysulfides. Complex structures with multiple components have been widely employed to address these issues by virtue of their strong polarity and abundant surface catalytic sites. Nevertheless, the tedious constructing procedures and high cost of these materials make the exploration of alternative high-performance sulfur hosts increasingly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 59 publications
1
46
0
1
Order By: Relevance
“…However, these non-polar carbon hosts have poor affinity for polar Li metal and dissolved polysulfides [ 24 27 ], resulting in loss of both electrode materials and rapid capacity fading during cycling processes. To enable the uniform deposition of Li metal and strong anchoring of polysulfides and Li 2 S, heteroatom doping (e.g., N, P, O, S, and B) [ 24 , 28 , 29 ], introduction of metal compounds (e.g., MnO 2 , MoS 2 , and VN) [ 30 33 ], and metal (e.g., Co, Ni, and Sn) [ 34 36 ] modifications have been widely applied to 3D carbon hosts to regulate their interfacial polarity. The interfacial doping of heteroatoms, especially dual-element doping, is simple and effective for stabilizing both electrodes during long-term cycling because of the strong and reversible interactions of the heteroatoms with metallic Li and Li 2 S n .…”
Section: Introductionmentioning
confidence: 99%
“…However, these non-polar carbon hosts have poor affinity for polar Li metal and dissolved polysulfides [ 24 27 ], resulting in loss of both electrode materials and rapid capacity fading during cycling processes. To enable the uniform deposition of Li metal and strong anchoring of polysulfides and Li 2 S, heteroatom doping (e.g., N, P, O, S, and B) [ 24 , 28 , 29 ], introduction of metal compounds (e.g., MnO 2 , MoS 2 , and VN) [ 30 33 ], and metal (e.g., Co, Ni, and Sn) [ 34 36 ] modifications have been widely applied to 3D carbon hosts to regulate their interfacial polarity. The interfacial doping of heteroatoms, especially dual-element doping, is simple and effective for stabilizing both electrodes during long-term cycling because of the strong and reversible interactions of the heteroatoms with metallic Li and Li 2 S n .…”
Section: Introductionmentioning
confidence: 99%
“…Throughout synthesizing a commonly available nitrogencontaining precursor via a templating strategy and subsequent removing nitrogen atoms, Guan et al reported an intrinsic defect-rich hierarchically porous carbon structure (DHPC). [102] The Raman signal ascribed to carbon defects at ≈1350 cm −1 for DHPC is stronger than that of the nitrogen-doped hierarchically porous carbon architecture (NHPC), indicating that the elimination of nitrogen atoms induced abundant carbon intrinsic defects (Figure 3c). Such defective carbon materials were further investigated by X-ray absorption near-edge structure (XANES) spectroscopy.…”
Section: Intrinsic Defectmentioning
confidence: 99%
“…Reproduced with permission. [102] Copyright 2020, American Chemical Society. Schematic of anion vacancy.…”
Section: Intrinsic Defectmentioning
confidence: 99%
“…Compared with traditional capacitors, it has larger capacity, specific energy or energy density, wider operating temperature range, and longer service life [24][25][26]. Although ultracapacitors are affected by voltage, current, temperature, and electrode materials [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], their cycle life is still long. With high energy density and high average output voltage, the aging of lithium batteries is a long-term gradual process [45][46][47], and their life is affected by temperature, current ratio, cutoff voltage, and other factors [48].…”
Section: Introductionmentioning
confidence: 99%